1977
DOI: 10.1111/j.1600-0447.1977.tb06679.x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study of affective disorders

Abstract: First and second degree relatives of 99 probands with affective disorders (49 unipolar and 50 bipolar subjects) were studied. The high risk values obtained for affective disorders were shown to be compatible with those found by other authors, although the prevalence of the illness in the population of Lombardy appears to be much lower than in other countries. Very low rates of suicide and alcoholism were found in our sample. Data obtained by analysis of the affected pairs of relatives rule out the hypothesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 27 publications
6
17
1
1
Order By: Relevance
“…Although the quality of the data for second-degree relatives was not as strong as for first-degree relatives, these estimates suggest that risks are comparable to population risks, i.e., 0.4-1.1% risk of bipolar I or II disorder and 3.6-5.4% risk of unipolar disorder among relatives of bipolar probands. The absence of elevated risks of these disorders among second-degree relatives was also observed in an earlier study [Smeraldi et al, 1977].…”
Section: Family Studiessupporting
confidence: 52%
“…Although the quality of the data for second-degree relatives was not as strong as for first-degree relatives, these estimates suggest that risks are comparable to population risks, i.e., 0.4-1.1% risk of bipolar I or II disorder and 3.6-5.4% risk of unipolar disorder among relatives of bipolar probands. The absence of elevated risks of these disorders among second-degree relatives was also observed in an earlier study [Smeraldi et al, 1977].…”
Section: Family Studiessupporting
confidence: 52%
“…In family studies an excess of unipolar and bipolar illness is usually found among the relatives of bipolar probands, whereas for unipolar probands the excess is predominantly of unipolar illness; in the summary of Smeraldi et al (1977) the ratio of unipolar to bipolar first-degree relatives is 178 for unipolar probands and 1 -63 for bipolar: Gershon et al (1982) give comparable figures of 10-8 and 1-3 for previous studies and 5-7 and 1-9 for their own. This difference could represent a liability for unipolar illness to become bipolar between generations.…”
Section: The Continuum Of Psychosissupporting
confidence: 65%
“…Several studies have suggested the possibility of a single dominant gene located on the X-chromosome in the bipolar group (Reich et al 1969;Winokur and Tanna 1969;Mendlewicz et al 1972a;Mend.lewicz and Rainer 1974). Other researchers (Green et al 1973;Goetzl et al 1974;Smeraldi et al 1977) are not in agreement with this. Other studies support an X-linked transmission, but only in the unipolar group (Perris 1966;Singh and Agrawal 1980).…”
Section: Epidemiology Of Denressioncontrasting
confidence: 42%
“…A number of studies (Perris 1971;Smeraldi et al 1977;Singh and Agrawal 1980) have reported data consistent with a polygenic pattern of inheritance for affective illness.…”
Section: Epidemiology Of Denressionmentioning
confidence: 91%